2006
DOI: 10.1111/j.1834-7819.2006.tb00399.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of silver fluoride and potassium iodide on the bond strength of auto cure glass ionomer cement to dentine

Abstract: drying is recommended as the clinical protocol for using AgF and KI on dentine surfaces prior to application of an auto cure glass ionomer cement.Key words: Dentine, bond strength, auto cure glass ionomer cement, silver fluoride, potassium iodide.Abbreviations and acronyms: AgF = diamine silver fluoride; ART = atraumatic restorative technique; GIC = glass ionomer cement; KI = potassium iodide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 9 publications
7
79
0
6
Order By: Relevance
“…This was attributed to physical and chemical interactions of SDF with calcium and albumin of the substrate and its reaction products inhibiting resin monomer infiltration. 29 However, in another study 35 using GIC, no effect on the bond strength to dentine was observed. Here, potassium iodide (KI) was applied after SDF to eliminate excess metallic silver in attempt to reduce discolouration.…”
Section: Silver Fluoridementioning
confidence: 97%
See 2 more Smart Citations
“…This was attributed to physical and chemical interactions of SDF with calcium and albumin of the substrate and its reaction products inhibiting resin monomer infiltration. 29 However, in another study 35 using GIC, no effect on the bond strength to dentine was observed. Here, potassium iodide (KI) was applied after SDF to eliminate excess metallic silver in attempt to reduce discolouration.…”
Section: Silver Fluoridementioning
confidence: 97%
“…It has been called: ''ammoniated silver fluoride'', 29 ''ammoniacal silver fluoride'', 19 ''silver fluoride diamine'', 30 ''diamine silver fluoride'', 31 ''diamine silver fluoride (AgF: (NH 3 ) 2 AgF)'', 32,33 ''diamine silver fluoride, referred to as AgF'', 34,35 ''silver diamine fluoride'', 20,22,24,25,36 ''diammine silver fluoride'' 37 and ''silver diammine fluoride''. 23,38 Firstly, it should be noticed that ''ammoniacal silver fluoride'' is a vague term and thus is inaccurate because the amount of ammonia was not specified.…”
Section: Nomenclature Of Silver Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The suggested explanation is that the silver ions from the SDF solution will react with the iodide ions from the KI solution to form silver iodide. It was reported that the application of SDF + KI to dentine surfaces before the placement of GIC restorations did not affect the bond strength of GIC to dentine [16], and did not adversely interfere with the fluoride uptake into the adjacent demineralised dentine [15]. It would be desirable if KI could inhibit the staining formation associated with SDF without diminishing its effectiveness in preventing and arresting dental caries.…”
Section: Introductionmentioning
confidence: 99%
“…Adhesion values similar to those of non-treated dentin were generated after such treatment. [9,10] Ariffin et al studied the release of fluoride by glass ionomer cement after coating with silver fluoride. They concluded that the application of a layer of 10% silver fluoride improves the concentration of fluoride released from this material.…”
Section: Discussionmentioning
confidence: 99%